Loneliness in Treatment-Seeking Substance-Dependent Populations: Validation of the Social and Emotional Loneliness Scale for Adults–Short Version. Issue 4 (2nd October 2018) - Ingram, Isabella; Kelly, Peter J.; Deane, Frank P.; Baker, Amanda L.; Raftery, Dayle K.
Abstract: Objectives: Loneliness is a distressing emotional experience that is likely to be prevalent among people accessing treatment for substance dependence problems. The first aim of the current study was to report on the validity of the Social and Emotional Loneliness Scale for Adults–Short Version (SELSA-S), a multidimensional measure of loneliness, for use in substance-dependent treatment populations. In order to further the understanding of loneliness among this population, loneliness was examined in relation to demographic, physical, and mental health variables.Methods: Participants were attending Australian residential substance dependence treatment services provided by two nongovernmental organizations (The Salvation Army and We Help Ourselves). Participants completed cross-sectional surveys ( N = 316) consisting of measures of demographics, substance use, loneliness, and physical and mental health.Results: Confirmatory factor analysis revealed high factor loadings and a moderate degree of concurrent and discriminant validity and internal consistency for the SELSA-S; however, model fit indices did not meet prespecified cutoff criteria. Loneliness was deemed to be a serious problem for 69% of respondents, and 79% reported feeling lonely at least once per month.Conclusions: Findings of this study suggest the need for further research into the validity of the SELSA-S for use with substance-dependent populations. In addition, it may be beneficial to test a range of loneliness measures in order to determine whether other measures of loneliness may be more favorable for use across this population.